Congenital deletion of Nedd4-2 in lung epithelial cells causes progressive alveolitis and pulmonary fibrosis in neonatal mice - Leitz, Dominik; Duerr, Julia; Mulugeta, Surafel; Seyhan Agircan, Ayça; Zimmermann, Stefan; Kawabe, Hiroshi; Dalpke, Alexander H.; Beers, Michael F.; Mall, Marcus A. (International journal of molecular sciences, 2021)
Recent studies found that expression of NEDD4-2 is reduced in lung tissue from patients with idiopathic pulmonary fibrosis (IPF) and that the conditional deletion of Nedd4-2 in lung epithelial cells causes IPF-like disease in adult mice via multiple defects, including dysregulation of the epithelial Na+ channel (ENaC), TGFβ signaling and the biosynthesis of surfactant protein-C proprotein (proSP-C). However, knowledge of the impact of congenital deletion of Nedd4-2 on the lung phenotype remains limited. In this study, we therefore determined the effects of congenital deletion of Nedd4-2 in the lung epithelial cells of neonatal doxycycline-induced triple transgenic Nedd4-2fl/fl/CCSP-rtTA2S-M2/LC1 mice, with a focus on clinical phenotype, survival, lung morphology, inflammation markers in BAL, mucin expression, ENaC function and proSP-C trafficking. We found that the congenital deletion of Nedd4-2 caused a rapidly progressive lung disease in neonatal mice that shares key features with interstitial lung diseases in children (chILD), including hypoxemia, growth failure, sterile pneumonitis, fibrotic lung remodeling and high mortality. The congenital deletion of Nedd4-2 in lung epithelial cells caused increased expression of Muc5b and mucus plugging of distal airways, increased ENaC activity and proSP-C mistrafficking. This model of congenital deletion of Nedd4-2 may support studies of the pathogenesis and preclinical development of therapies for chILD.
Gesehen am 07.09.2022